DOMS: Delayed onset muscle soreness. Definition and classification - Vitaterna, M. C. (EWF Scientific Magazine, 2019)
We have all experienced the unpleasant sensation of feeling pain when getting out of the car, going down the stairs, the difficulty of getting up off a chair or moving about normally after an intense workout. This type of pain is called Delayed Onset Muscle Soreness (DOMS) and is also known as EIMD. Those who have been training for a sufficiently long period of time have probably experienced it. Some athletes perceive this pain as an indicator of success, of good training, the article gives a look at what scientific evidence affirms. It is clear that, given that the causes are still unknown, even more so are the strategies for improving this particular condition. Therefore, there is not even a classification system that can provide the severity of the symptoms with a value. It is up to the practitioner, with theory and practice, to perceive what type of symptomatology it is. Assuming that a truly valid strategy for recovery has not yet been found, some scientific evidence is more encouraging than others. The most valid scientific strategies are: hot/cold therapy and heat, the integration of curcumin, caffeine, fatty acids (omega- 3), monohydrate creatine and taurine; in addition, improving sleep quality is one of the most valid strategies. Not unequivocal results concern massage therapy, NSAIDs and active recovery.